Edukasi Penanggulangan Hipertensi dan Pemanfaatan Bahan Alam Berbasis Kearifan Lokal pada Petani Jambu Biji Merah di Jatirejo, Ngargoyoso: Education on Hypertension Management and the Utilization of Local Wisdom-Based Natural Resources for Red Guava Farmers in Jatirejo, Ngargoyoso - Aulia Nur Rahmawati; Alip Desi Suyono Saputri; Truly Dian Anggraini; Bayu Kurniaaji; Pranichayudha Rohsulina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Farmers in Jatirejo Village, Ngargoyoso, under the P4S Putra Jambu association, play a dual role as guava cultivators and agritourism educators. High physical demands and unhealthy lifestyles, such as smoking and high sugar/salt intake, increase the risk of hypertension and occupational stress, potentially hindering their productivity. This community service aims to enhance farmers' knowledge and awareness of hypertension prevention through health education and the utilization of local natural resources. Methods: The program was conducted in October 2025 and involved 27 farmers. Methods included education using the "Menjadi Petani Sehat" pocketbook, interactive Q&A sessions, and medical check-ups (blood pressure, blood glucose, and uric acid). Evaluation was measured via pre-test, post-test, and satisfaction questionnaires. The activity resulted in a 46.2% increase in farmers' knowledge. Medical screenings revealed that 81.8% of farmers were at risk of hypertension (BP ≥ 130/80 mmHg), and 52.4% had elevated blood sugar and uric acid levels. Participants responded very positively, with an 83.21% satisfaction rate. Education and health screenings are effective in improving farmers' understanding of healthy living, which is crucial for supporting sustainable agriculture and agritourism in Jatirejo Village.